Functional state of autonomic nervous system, central hemodynamics, and physical work capacity in former track and field athletes - Mikhalyuk, Yevgen Leonidovich; Gunina, Larisa; Михалюк, Євген Леонідович (Vilnius, 2017)
The article presents comparative data o f complex functional state examining o f 24 highly skilled female athletes who were engaged in 100 to 400 m running at a young age. 12 females (group I) have been continuing active physical exercise training after withdrawal from competitive sport. Comparison group (group II) included 12 females who have been conducting a sedentary lifestyle after withdrawal from competitive running. The two main groups were compared considering the level o f sport skills. 12 females never engaged in any sports training with insufficient level of motor activity fo rm ed the control group.
Keywords: former athletes; track and field; heart rate variability; central hemodynamics; autonomic nervous; system; physical work capacity